Clinical profile of the patients with the intractable neurologic disorders in our hospital from 1984 to 1988 with reference to activities of daily living at admission and discharge - ADACHI Katsuhito; KIMURA Chiyomi; YONEDA Kenji; UEDA Yuriko; INOUE Tomoko; INUI Toshio; NOBORI Hideko; WATANABE Yaeko; TAKAI Akemi; MAEDA Sachiko; SATO Tamie; YAMAMOTO Tokiko (Japanese Journal of National Medical Services, 1989)
We studied the clinical profile of the inpatients with intractable neurologic disorders in Tokushima Byoin National Sanatorium from 1984 to 1988. The total number of the inpatients was 148 during these 5 years and the number has been increasing year by year. At present we have 54 patients. The mean numbers of the new inpatients and the discharged patients for one year were 25 and 19, respectively. The mean period of admisson about 94 discharged cases and 54 cases now in admission was 13 and 38 months, respectively. There were 26 dead cases and 9 autopsied cases (35%) for these 5 years. There were 44 (30%) cases of Parkinson disease (PD), 28 (19%) spinocerebellar degeneration (SCD), 19 (13%) amyotrophic lateral sclerosis (ALS), 21 (14%) motor neuron disease except ALS (MND) and others.At admission to our hospital, the number of bed-ridden patients was 97 (65%). In activities of daily living during admissoin, 13 patients out of 33 PD patients showed improvement, 13 out of 15 ALS patients showed progression and 12 of them died, and 9 out of 12 SCD patients and 11 out of 14 MND patients did not show any changes. 本院入院の過去5年間の神経難病患者(148例)の実態を示す. 神経難病患者の在院患者数は毎年増加し現在54例である. 各年の新入院患者数は平均25例, 退院者は19例であつた. 本症の総退院患者94例の在院期間は平均13ヵ月であり, 現入院患者では平均38ヵ月にも及んでいる. 死亡例は5年間で26例, うち剖検例は9例(35%)であつた. 疾患別では, パーキンソン病(PD)が最も多く44例(30%), 次いで脊髄小脳変性症(SCD)が28例(19%), 筋萎縮性側索硬化症(ALS)が19例(13%), ALS以外の運動ニユーロン病(MND)が21例(14%)などであつた. これら患者の入院時の日常生活動作(ADL)は, ベツト上での生活を強いられている患者が97例(65%)と著しく障害されていた. さらに上記4疾患について退院時と比較してみると, 改善例はPDにのみ33例中13例にみられ, 悪化例はALSで15例中13例(うち死亡例12例)であつた. 不変例はSCDとMNDで多く, それぞれ12例中9例, 14例中11例であつた.